2011
DOI: 10.1038/nsmb.2055
|View full text |Cite
|
Sign up to set email alerts
|

Structural adaptation of the plant protease Deg1 to repair photosystem II during light exposure

Abstract: Deg1 is a chloroplastic protease involved in maintaining the photosynthetic machinery. Structural and biochemical analyses reveal that the inactive Deg1 monomer is transformed into the proteolytically active hexamer at acidic pH. The change in pH is sensed by His244, which upon protonation, repositions a specific helix to trigger oligomerization. This system ensures selective activation of Deg1 during daylight, when acidification of the thylakoid lumen occurs and photosynthetic proteins are damaged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 19 publications
3
112
1
Order By: Relevance
“…In particular, evidence exists that the activity of the STN8 kinase is dependent on the redox state of the plastoquinone pool [39,55]. Furthermore, the active forms of the FtsH and Deg proteases are hexamers [45,46,50]. For the Deg protease, it was found that oligomerization is triggered by acidic pH values in the thylakoid lumen [50].…”
Section: Psii Repair Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, evidence exists that the activity of the STN8 kinase is dependent on the redox state of the plastoquinone pool [39,55]. Furthermore, the active forms of the FtsH and Deg proteases are hexamers [45,46,50]. For the Deg protease, it was found that oligomerization is triggered by acidic pH values in the thylakoid lumen [50].…”
Section: Psii Repair Cyclementioning
confidence: 99%
“…Furthermore, the active forms of the FtsH and Deg proteases are hexamers [45,46,50]. For the Deg protease, it was found that oligomerization is triggered by acidic pH values in the thylakoid lumen [50]. As such, the structural rearrangements of thylakoid membranes should be seen as part of a complex regulatory network that controls the repair processes in thylakoid membranes.…”
Section: Psii Repair Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in Section 1, the crystal structure of Deg1 contains a protease domain at the N-terminal and a PDZ domain at the C-terminal (see also Figure 2a) (Kley et al, 2011). When the structure of Deg5 was modeled using SWISS-MODEL with Deg1 as the template, we found that Deg5 was composed of 1 domain (residues 81-322) that encompassed 2 perpendicular β-barrel lobes with Nand C-terminal helices (helices H1 and H2) (Figure 2b).…”
Section: The Modeled Structure Of Deg5mentioning
confidence: 99%
“…All of them possess a conservative AAA + domain which is responsible for ATP binding and hydrolysis, necessary to unfold protein substrates so that they can enter a catalytical chamber of the proteases molecule through a narrow entrance [1]. Nevertheless, some other proteases, including the Deg group, function in an ATP-independent manner, most probably because the availability of catalytic center is less restricted for unfolded substrates than in the case of ATP-dependent enzymes [2].…”
Section: Introductionmentioning
confidence: 99%